Oxidative Stress Is Associated with an Increased Antioxidant Defense in Elderly Subjects: A Multilevel Approach - Flores-Mateo, Gemma; Elosua, Roberto; Rodriguez-Blanco, Teresa; Basora-Gallisà, Josep; Bulló, Mònica; Salas-Salvadó, Jordi; Martínez-González, Miguel Ángel; Estruch, Ramon; Corella, Dolores; Fitó, Montserrat; Fiol, Miquel; Arós, Fernando; et al. (PloS one, 2014)
Studies of associations between plasma GSH-Px activity and cardiovascular risk factors have been done in humans, and contradictory results have been reported. The aim of our study was to assess the association between the scavenger antioxidant enzyme glutathione peroxidase (GSH-Px) activity in plasma and the presence of novel and classical cardiovascular risk factors in elderly patients. We performed a cross-sectional study with baseline data from a subsample of the PREDIMED (PREvención con DIeta MEDiterránea) study in Spain. Participants were 1,060 asymptomatic subjects at high risk for cardiovascular disease (CVD), aged 55 to 80, selected from 8 primary health care centers (PHCCs). We assessed classical CVD risk factors, plasma oxidized low-density lipoproteins (ox-LDL), and glutathione peroxidase (GSH-Px) using multilevel statistical procedures. Mean GSH-Px value was 612 U/L (SE: 12 U/L), with variation between PHCCs ranging from 549 to 674 U/L (Variance =  013.5; P<0.001). Between-participants variability within a PHCC accounted for 89% of the total variation. Both glucose and oxidized LDL were positively associated with GSH-Px activity after adjustment for possible confounder variables (P = 0.03 and P = 0.01, respectively). In a population at high cardiovascular risk, a positive linear association was observed between plasma GSH-Px activity and both glucose and ox-LDL levels. The high GSH-Px activity observed when an oxidative stress situation occurred, such as hyperglycemia and lipid oxidative damage, could be interpreted as a healthy defensive response against oxidative injury in our cardiovascular risk population.